2012
DOI: 10.1145/2185520.2185587
|View full text |Cite
|
Sign up to set email alerts
|

Render me real?

Abstract: Figure 1: Male avatar rendered in different visual styles, ranging from realistic to abstract, based on the results in Section 5. AbstractThe realistic depiction of lifelike virtual humans has been the goal of many movie makers in the last decade. Recently, films such as Tron: Legacy and The Curious Case of Benjamin Button have produced highly realistic characters. In the real-time domain, there is also a need to deliver realistic virtual characters, with the increase in popularity of interactive drama video g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(47 citation statements)
references
References 20 publications
1
46
0
Order By: Relevance
“…They observed high correlation between professional appearances in avatar design with high credibility measures. McDonnell et al (2012) showed that small differences in rendering styles can influence perceptual judgments of computer graphic characters. Hyde et al (2015) found that adjusting the expressiveness of interactive animated avatars may be a simple way to influence people's social judgments and willingness to collaborate with animated avatars.…”
Section: Avatarmentioning
confidence: 99%
“…They observed high correlation between professional appearances in avatar design with high credibility measures. McDonnell et al (2012) showed that small differences in rendering styles can influence perceptual judgments of computer graphic characters. Hyde et al (2015) found that adjusting the expressiveness of interactive animated avatars may be a simple way to influence people's social judgments and willingness to collaborate with animated avatars.…”
Section: Avatarmentioning
confidence: 99%
“…This definition encapsulates the two main continuums of interest when considering a virtual human: its visual realism (McDonnell, Breidt, & Bülthoff, 2012) and its behavioral realism (von der Pütten et al). Visual realism can be influenced by a number of factors, including rendering style (McDonnell et al, 2012), animation quality (Maddock, Edge, & Sanchez, 2005), display characteristics (e.g. resolution, size) (Ni, Bowman, & Chen, 2006), and display modality (e.g.…”
Section: Types Of Virtual Humansmentioning
confidence: 99%
“…Nowak et al found that agents with low anthropomorphism (a highly stylized cartoon face) evoked stronger feelings of social presence than high anthropomorphism agents (Nowak & Biocca, 2003). McDonnell et al found that participants rated cartoon faces with lower realism as more appealing and more friendly than slightly more realistic faces (McDonnell et al, 2012); however, highly realistic faces were rated as similarly appealing and friendly. Ring et al found an interaction effect between task domain (medicine vs. social dialog) and visual realism on how an agent was perceived (Ring et al); less realistic virtual humans were perceived as more likable in the social domain, but not in the medical.…”
Section: Types Of Virtual Humansmentioning
confidence: 99%
“…Although there have been great advances in modeling, rigging, rendering, motion capture and retargeting techniques -with the goal of escaping the "Uncanny Valley" (Alexander, Rogers, Lambeth, Chiang, & Debevec, 2009;McDonnell, Breidt, & Bülthoff, 2012) -the creation of realistic and convincing face behaviors for games and movies is still strongly dependent on animator skills. There are some studies about how to convey and evaluate a character's complex facial behaviors (Paleari & Lisetti, 2006;Bevacqua, Mancini, Niewiadomski, & Pelachaud, 2007;Rehm, 2008;Orvalho & Sousa, 2009;Niewiadomski, Hyniewska, & Pelachaud, 2009;Queiroz, Braun, et al, 2010;Demeure, Niewiadomski, & Pelachaud, 2011;de Melo, Carnevale, & Gratch, 2011;Xolocotzin Eligio, Ainsworth, & Crook, 2012), but few really focus on microexpressions (Zielke, Dufour, & Hardee, 2011).…”
Section: Introductionmentioning
confidence: 99%